Measuring service quality / Rosliza Md Zani ... [et al.] - Md Zani, Rosliza; Ramli, Abd Rasyid; Mohd Saad, Shakirah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Quality of a service can be understood as a comprehensive customer evaluation of a particular service and the extent to which it meets their expectations and provides satisfaction. It is one of the crucial factors that determines the success of an organization by which the organization needs to integrate all business functions towards meeting every customer's expectations. To achieve these capabilities, the organization must be equipped with criteria and meet certain requirements as a facilitator in improving and maintaining the quality of service. (Berinyuy & Daniel, 2010).